O pensamento de Martin Heidegger e o Direito (em tempos de biopolítica) - Aquino, Márcia Regina Pitta Lopes (2015)
This is a theoretical research whose purpose is to demonstrate that one lives today in times of radicalizated biopolitics as a result of the modern technic essence domain as understood by Martin Heidegger. It presents some aspects of Michel Foucault s thought and Giorgio Agamben s thought about biopolitics. It follows Martin Heidegger s trajectory of thought, especially in his second phase when, with the introduction of the notion of Gestell, he demonstrates the meaning of the modern technic essence as a way of common-belonging of man and being. It shows that only in a po(i)etic common-belonging between man and being, the man can keep his human essence. It presents the Willis Santiago Guerra Filho s thesis about the imaginary knowledge of law as an example of an understanding about it that corresponds to that keeping, in order to improve legal effectiveness